2020
DOI: 10.1080/16078454.2020.1769419
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre retrospective study of primary breast diffuse large B-cell and high-grade B-cell lymphoma treatment strategies and survival

Abstract: Objectives:: Primary breast diffuse large B-cell lymphoma (PB-DLBCL) and primary breast highgrade B-cell lymphoma (PB-HGBCL) are rare extranodal aggressive B-cell lymphomas with distinct characteristics. Reliable data regarding appropriate treatment of these specific entities are lacking due to their rarity. Methods:: We reviewed 36 patients diagnosed at four Chinese medical centres between January 2008 and December 2018. Data regarding clinicopathological features, therapeutic evaluation and central nervous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Interestingly, only 24% of these cases received adjuvant RT, 5-year PFS was over 70% with remissions continuing to 9 years. 32 The opposite sequence of therapy, systemic prior to tumordirected therapy, was reported in the majority of over 2000 cases of Stages I and II PBL in group studies. CHOP, or later rituximab-CHOP (R-CHOP), has typically been given for 4 to 6 cycles and followed by radiation of the tumor.…”
Section: Combination Treatmentmentioning
confidence: 99%
“…Interestingly, only 24% of these cases received adjuvant RT, 5-year PFS was over 70% with remissions continuing to 9 years. 32 The opposite sequence of therapy, systemic prior to tumordirected therapy, was reported in the majority of over 2000 cases of Stages I and II PBL in group studies. CHOP, or later rituximab-CHOP (R-CHOP), has typically been given for 4 to 6 cycles and followed by radiation of the tumor.…”
Section: Combination Treatmentmentioning
confidence: 99%
“…Multiple studies have been reported, but no definitive schedule has been established to improve the outcomes. [2][3][4][5][6][7][8][9][10] The role of radiotherapy has not been determined.…”
Section: Introductionmentioning
confidence: 99%